STRATEGI KEBIJAKAN PEMBANGUNAN DAERAH KABUPATEN PUNCAK JAYA PENDEKATAN ANALISIS SWOT DAN AHP - Wonerengga, Lesmin; K, Duha Awaluddin; Bachtiar, Petrus (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
Factors that influence the regional development of Puncak Jaya Regency, namely: strength factor: Puncak Jaya Regency as a mining area with Potential C Excavated Tax and Ground Water Source Assets. Weakness factor: Lack of efforts to socialize the potential of the Puncak Jaya Regency area to outsiders. The level of community participation in planning, implementing, and supervising regional development is still lacking. Opportunity factor: Various central and local governments of Puncak Jaya Regency. Threat factors: ASEAN-China Free Trade Area (ACFTA), Globalization, free market, and world economic openness, lack of private investment in Puncak Jaya Regency. The priority strategies for regional development policies for Puncak Jaya Regency are based on consideration of potential, capabilities, and existing constraints, namely: Alternative strategies include making the best possible use of financial support from the central government to maximize the potential that exists in the region. Maximizing the local tax sector and groundwater resource assets. The development policy priorities are: strengthening micro-economy, utilizing all resource to optimize regional autonomy, and improving institutional performance.